The aspect of the verb as a grammatical category in the Polish and German language editions of ‘Piękni dzwudziestoletni’ by Marek Hłasko - Niewada, Michał (Free your mind: Reflections on language, literature and culture, 2022)
The aim of this paper is to analyse the translatability of the grammatical category of verb’s aspect in German on the basis of selected fragments of the Polish- and German-language editions of ‘Piękni dwudziestoletni’ by Marek Hłasko. The detailed analysis concerns the translation methods chosen by the translator Roswitha Matwin-Buschmann and how they convey the Polish verb’s aspectual character in the German translation of the book. The following article answers the question of which translation methods, if any, enable the reflection of the verb’s aspect in German, which is devoid of it.